THE DEVELOPMENT OF A GUIDEBOOK FOR DESIGNING INTERACTIVE DISTANCE LEARNING (PIJAR) FOR LECTURERS OF TECHNOLOGY AND VOCATIONAL EDUCATIONAL DEPARTEMENT - Pancawati, Ratna (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2021)
The research aims at developing a guidebook for designing interactive distance learning for lecturers, considering that lecturers need guidance on how to design a learning implementation process that remains interactive in a full online learning system during the Covid 19 pandemic. The development of a guidebook stage adopted the model of Dick & Carey which modified into 4 stages, namely stages; (1) requirement analysis; (2) product design; (3) validation and evaluation; and (4) product revision. Based on development result, data found as follows; (1) the expert's assessment shows that the guidebook is included in the criteria of